Seroprevalence of human immunodeficiency virus, hepatitis B and C viruses and syphilis infections among blood donors at the Muhimbili National Hospital in Dar Es Salaam, Tanzania - Lyamuya Eligius F; Magesa Pius M; Matee Mecky IN (BMC, 2006)
Abstract Background According to the latest Tanzanian National AIDS Control Programme (NACP) report a total of 147,271 individuals donated blood during the year 2002. However, blood safety remains an issue of major concern in transfusion medicine in Tanzania where national blood transfusion services and policies, appropriate infrastructure, trained personnel and financial resources are inadequate. Most of the donated blood is screened for HIV alone. Methods We determined among blood donors at Muhimbili National Hospital (MNH), the seroprevalence of human immunodeficiency virus (HIV), hepatitis C virus (HCV), hepatitis B surface antigen (HBsAg) and syphilis by donor type, sex and age and to determine association, if any, in the occurrence of the pathogens. The sample included 1599 consecutive donors, 1424(89.1%) males and 175 (10.9%) females, who donated blood between April 2004 and May, 2005. Most of them 1125 (70.4%) were replacement donors and a few 474 (29.6%) voluntary donors. Their age (in years) ranged from 16 to 69, and most (72.2%) were between 20-39 years. Results Two hundred and fifty four (15.9%) of the donated blood had serological evidence of infection with at least one pathogen and 28 (1.8%) had multiple infections. The current seroprevalence of HIV, HBsAg, HCV and syphilis among blood donors at MNH in Dar es Salaam was found to be 3.8%, 8.8%, 1.5% and 4.7%, respectively. Respective seroprevalences among HIV seronegative blood donors were 8.7% for HBV, 1.6% for HCV and 4.6% for syphilis. The differences in the prevalence of HIV and syphilis infections between replacement and voluntary donors were statistically significant (P < 0.05). Syphilis was the only infection that occurred more frequently among HIV infected (12.1%) than non-infected (4.6%) blood donors (P < 0.05), and whose prevalence increased with age (X2 = 58.5 df = 5, P < 0.001). There were no significant sex differences in the occurrence of pathogens. Finally, there were significant associations in the occurrence of HBsAg and syphilis (OR = 2.2, 95% CI 1.1.-4.2) and HIV and syphilis (OR = 2.2, 95% CI 1.0-5.3). Conclusion The high (15.9%) seroprevalence of blood-borne infections in blood donated at MNH calls for routine screening of blood donors for HBV, HCV, HIV and syphilis and for strict selection criteria of donors, with emphasis on getting young voluntary donors and for establishment of strict guidelines for blood transfusions.